2021
DOI: 10.7150/thno.64601
|View full text |Cite
|
Sign up to set email alerts
|

CLEC-2-dependent platelet subendothelial accumulation by flow disturbance contributes to atherogenesis in mice

Abstract: Rationale: Platelets play an essential role in atherosclerosis, but the underlying mechanisms remain to be addressed. This study is to investigate the role of platelets in d-flow induced vascular inflammation and the underlying mechanism. Methods: We established a disturbed blood flow (d-flow) model by partial carotid ligation (PCL) surgery using atherosclerosis-susceptible mice and wild-type mice to observe the d-flow induced platelet accumulation in the subendothelium or in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…130 Under shear stress, PECAM-1 (platelet EC adhesion molecule 1) and CLEC-2 also mediate platelet adhesion to ECs. [131][132][133] In the study by Ilkan et al, 134 the authors showed the presence of Piezo1 mechanosensitive ion channel in human platelets and megakaryocytes. D-flow in the arteries stimulates platelets and Meg-01 (megakaryocytes cell line) Ca 2+ proving the presence of mechanosensitive cation channels.…”
Section: Biomechanical Platelet Activation and Platelets As A Mechano...mentioning
confidence: 99%
See 1 more Smart Citation
“…130 Under shear stress, PECAM-1 (platelet EC adhesion molecule 1) and CLEC-2 also mediate platelet adhesion to ECs. [131][132][133] In the study by Ilkan et al, 134 the authors showed the presence of Piezo1 mechanosensitive ion channel in human platelets and megakaryocytes. D-flow in the arteries stimulates platelets and Meg-01 (megakaryocytes cell line) Ca 2+ proving the presence of mechanosensitive cation channels.…”
Section: Biomechanical Platelet Activation and Platelets As A Mechano...mentioning
confidence: 99%
“…141 Platelets in atherosclerosis also showed the expression of receptors like PECAM-1 and CLEC-2 mediating their accumulation in sub-endothelium and ameliorating plaque formation in mice models. 133,134…”
Section: Biomechanical Platelet Activation and Platelets As A Mechano...mentioning
confidence: 99%
“…Pdpn was specifically associated with lymphatic endothelium number of adventitial lymphatics of human internal carotid artery, which demonstrated Pdpn may participate in atherosclerosis via regulating functions and regeneration of adventitial lymphatic vessels in atherosclerotic lesions ( 41 ). In a disturbed blood flow (d-flow) model, monocyte Pdpn was upregulated by d-flow, and the myeloid-specific Pdpn deletion mitigated the subendothelial accumulation of platelets and monocytes/macrophages, which ameliorated vascular inflammation ( 42 ) ( Table 1 ).…”
Section: Pdpn In Atherosclerosismentioning
confidence: 99%
“…Interestingly, pro-inflammatory cytokines were found to enhance Pdpn expression in stromal and endothelial cells, further supporting a correlation between inflammation and podoplanin functions in atherosclerotic plaques ( Gröger et al, 2004 ; Suzuki et al, 2008 ). In a disturbed blood flow (d-flow) model, monocyte Pdpn was upregulated by d-flow, and myeloid-specific Pdpn deletion mitigated the subendothelial accumulation of platelets and monocytes/macrophages ( Tang et al, 2021 ). All these suggest that Pdpn may contribute to the atherosclerosis development in both CLEC-2-dependent and independent manners.…”
Section: Relevance Of Podoplanin To Diseasesmentioning
confidence: 99%